Estimação de parâmetros genéticos e análise de trilha para caracteres da arquitetura da planta de feijão caupi (Vigna unguiculata (L.) Walp.) - Ribeiro, Hugo Leonardo Coelho (2012)
The development of cowpea plants with architecture suitable for full mechanization is in early stage and it is important in order to expand cultivation of cowpea. Genetic parameters were estimated by the mean and variance of segregating and not segregating generations of a cross between BRS Carijó, erect type, and BR14 Mulato, climbing prostrate type, for traits related to maturity (DFM) and plant architecture in order to guide the development of cowpea cultivars for mechanical or semi mechanical harvesting. For the plant architecture, the characters length of the main branch (MBL), length of the longest secondary branch (SBL), number of secondary branch (SBN), number of nodes in the main branch (MBN), plant type and habit growth were analyzed. The means of parents were contrasting for all traits. The broad and narrow heritabilities were close to or superiors to 50% for all characters. The effects of parent means and additive allele effects were important for the characters MBL, MBN and DFM, while for the characters SBL and SBN the contribution of epistatic effects were also important. The plant type and growth habit exhibited monogenic inheritance in dominance. For all traits, was estimated a reduced number of genes. The results indicated that the development of varieties with plant architecture suitable for mechanical or semi mechanical harvesting can be obtained relatively easily by methods widely used in selfedplants.